2008
DOI: 10.1002/pmic.200700460
|View full text |Cite
|
Sign up to set email alerts
|

Long term anoxia in rainbow trout investigated by 2‐DE and MS/MS

Abstract: Twenty-four hours of N 2 induced anoxia induced global perturbations on protein expression in rainbow trout hypodermal fibroblasts cell line. Anoxia was obtained by depleting the medium of O 2 by flushing with N 2 , and protein changes were studied by 2-DE coupled with MS providing quantitative measurements of a large number of proteins in one single study. The anoxic insult changed the level of 33 protein spots: 22 of these were up-regulated compared to the control situation and 11 were down-regulated. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 79 publications
(80 reference statements)
1
23
1
Order By: Relevance
“…An increase in hepatic PGM1 has been found in gilthead sea bream fed maslinic acid, indicating a stimulation of glycogen metabolism (Rufino-Palomares et al, 2011). An up-regulation of PGM1 has also been obtained in fish as response to longterm anoxia (Wulff et al 2008). Another study done on cytotrophoblasts, reported an increase in PGM1 as response to hypoxia (Hoang et al 2001).…”
mentioning
confidence: 74%
“…An increase in hepatic PGM1 has been found in gilthead sea bream fed maslinic acid, indicating a stimulation of glycogen metabolism (Rufino-Palomares et al, 2011). An up-regulation of PGM1 has also been obtained in fish as response to longterm anoxia (Wulff et al 2008). Another study done on cytotrophoblasts, reported an increase in PGM1 as response to hypoxia (Hoang et al 2001).…”
mentioning
confidence: 74%
“…Stress related to farming conditions [26][27][28] has been one of the main themes reported in studies with these species and also in other less studied species like gilthead seabream (Sparus aurata) [29], together with muscle quality [30][31][32][33]. Related to fish quality is the work on understanding the mechanisms involved in the development of skeletal malformations of the vertebral column of normal and deformed white seabream (Diplodus sargus) by comparative proteomic analysis [34].…”
Section: Vertebratesmentioning
confidence: 99%
“…The study of the impact of xenobiotics in aquaculture has also benefited from proteomics technologies, with several studies done on the impact of biotoxins [141,[151][152][153], pharmaceuticals [58,154,155], hormones [15,46,156], metals [157,158] and other pollutants [43,45,67,[159][160][161][162][163] on the proteomes of aquaculture aquatic organisms. Finally, there are also some studies correlating environmental sources of stress in aquaculture (hypoxia [57], anoxia [26,[164][165][166], hyperoxygenation [167], osmotic [168][169][170][171][172][173] and temperature [174][175][176][177], as well as stress induced by management practices (like high stocking densities [29,178], handling [29,179] and pre-slaughter stress [180]), with proteome changes in several tissues.…”
mentioning
confidence: 98%
“…-dependent cysteine proteinases implicated with pro-and anti-apoptotic functions in mammals [75]. So far, it has been documented that calpains and the related regulatory protein calpastatin are differentially expressed in starving trout [76,77], in developing zebrafish [78], and in trout hepatocytes exposed to anoxia in vitro [79], where an increase in calpain activity might facilitate apoptosis by cleavage of anti-apoptotic proteins [80].…”
Section: Other Executioners and Regulators Of Apoptosismentioning
confidence: 99%